Aktualisasi diri dalam filsafat eksistensialisme relevansinya bagi pendidikan abad 21 - Ulfah, Siti Zayyana; Syihabuddin, Syihabuddin; Kembara, Maulia Depriya (Universitas Negeri Yogyakarta, 2025)
Education is an essential foundation in character building and human potential development that lasts throughout life. In the modern era, education not only acts as a transfer of knowledge, but also as a medium to help individuals achieve full self-actualization. This research explores the relevance of existentialism philosophy in the context of 21st century education, focusing on self-actualization as the core of individual development. This research uses the literature method to understand the application of existentialism principles, such as freedom, authenticity, responsibility, and the search for the meaning of life in education. The results show that existentialism-based education supports the holistic development of students' potential through self-confidence, active engagement and character strengthening. In addition, education that integrates spiritual values offers a comprehensive approach to address modern challenges, such as academic pressures, emotional needs, and the influence of technology. With this approach, students are expected to be able to face the challenges of the modern era with strong character, high integrity, and a balance between worldly and spiritual achievements. This research makes an important contribution to the development of humanist and contextualized education, according to the demands of the 21st century. Pendidikan adalah landasan esensial dalam pembentukan karakter dan pengembangan potensi manusia yang berlangsung sepanjang hayat. Dalam era modern, pendidikan tidak hanya berperan sebagai transfer ilmu, tetapi juga sebagai medium untuk membantu individu mencapai aktualisasi diri secara utuh. Penelitian ini mengeksplorasi relevansi filsafat eksistensialisme dalam konteks pendidikan abad ke-21, dengan fokus pada aktualisasi diri sebagai inti pengembangan individu. Penelitian ini menggunakan metode kepustakaan untuk memahami penerapan prinsip-prinsip eksistensialisme, seperti kebebasan, autentisitas, tanggung jawab, dan pencarian makna hidup dalam pendidikan. Hasil penelitian menunjukkan bahwa pendidikan berbasis eksistensialisme mendukung pengembangan potensi siswa secara holistik melalui kepercayaan diri, keterlibatan aktif, dan penguatan karakter. Selain itu, pendidikan yang mengintegrasikan nilai-nilai spiritualitas menawarkan pendekatan komprehensif untuk menjawab tantangan modern, seperti tekanan akademis, kebutuhan emosional, dan pengaruh teknologi. Dengan pendekatan ini, siswa diharapkan mampu menghadapi tantangan era modern dengan karakter kuat, memiliki integritas tinggi, serta keseimbangan antara pencapaian duniawi dan spiritual. Penelitian ini memberikan kontribusi penting dalam pengembangan pendidikan yang humanis dan kontekstual, sesuai tuntutan abad ke-21.